Responsible Tourism Consumption in Thailand: eWOM’s Role - ERAWAN, Theera; KRAIRIT, Donyaprueth (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020, 2020)
This paper examines the effects of electronic word-of-mouth (eWOM) on responsible tourism consumption behavior, based on the theory of planned behavior (TPB) and empirical investigation. A three-pronged approach (a cross validation technique involving a literature review, expert interviews, and an exploratory field study) was employed to obtain reliable and valid results. Structural equation modeling (SEM) was utilized to confirm the conceptual framework and hypotheses. Findings revealed a positive relationship between perceived behavioral control (PBC) and intention. Intention’s mediating role in responsible tourism consumption was also supported. eWOM’s positive, indirect effect on responsible tourism consumption emerged apart from the literature. The outcomes provide useful information for governments, the private sector, and civil society in planning and implementing sustainable consumption activities to achieve overall development for sustainable tourism. By proposing a conceptual framework based on TPB and utilizing the three-pronged approach, eWOM’s effects emerged as a valid extension of TPB. This study is among the first to be conducted in developing country and in the context of tourism in Thailand, where the primary focus is Sustainable Development Goal (SDG) #12: responsible consumption and production.